The Potential of Phenothiazines against Endodontic Pathogens: A Focus on Enterococcus-Candida Dual-Species Biofilm - Nicole de Mello Fiallos; Ana Luiza Ribeiro Aguiar; Bruno Nascimento da Silva; Mariana Lara Mendes Pergentino; Marcos Fábio Gadelha Rocha; José Júlio Costa Sidrim; Débora Castelo Branco de Souza Collares Maia; Rossana de Aguiar Cordeiro (MDPI AG, 2022)
Persistent apical periodontitis occurs when the endodontic treatment fails to eradicate the intraradicular infection, and is mainly caused by Gram-positive bacteria and yeasts, such as Enterococcus faecalis and Candida albicans, respectively. Phenothiazines have been described as potential antimicrobials against bacteria and fungi. This study aimed to investigate the antimicrobial potential of promethazine (PMZ) and chlorpromazine (CPZ) against E. faecalis and C. albicans dual-species biofilms. The susceptibility of planktonic cells to phenothiazines, chlorhexidine (CHX) and sodium hypochlorite (NaOCl) was initially analyzed by broth microdilution. Interaction between phenothiazines and CHX was examined by chequerboard assay. The effect of NaOCl, PMZ, CPZ, CHX, PMZ + CHX, and CPZ + CHX on biofilms was investigated by susceptibility assays, biochemical and morphological analyses. Results were evaluated through one-way ANOVA and Tukey's multiple comparison post-test. PMZ, alone or in combination with irrigants, was the most efficient phenothiazine, capable of reducing cell counts, biomass, biovolume, carbohydrate and protein contents of dual-species biofilms. Neither PMZ nor CPZ increased the antimicrobial activity of CHX. Further investigations of the properties of phenothiazines should be performed to encourage their use in endodontic clinical practice.